RANCANGAN DOKUMEN SOP TERKAIT TUGAS PERSONEL AMBULANS SESUAI KOMPETENSI GUNA OPTIMALISASI FUNGSI YANG MENUNJANG OPERASI ARFF DI BANDAR UDARA KUALANAMU DELI SERDANG - Leony Serbinakrist Br. Sinuraya; Lina Rosmayanti; Alwazir Abdusshomad (MANAJEMEN, 2025)
This study is motivated by the absence of a specific Standard Operating Procedure (SOP) that regulates the roles of ambulance personnel in supporting Aircraft Rescue and Fire Fighting (ARFF) operations at Kualanamu International Airport, especially in handling emergencies such as aircraft crashes. The research method used is Research and Development (R&D) level 1, with data collected through documentation studies, interviews, and direct observation during On the Job Training (OJT) at the ARFF unit. The results show that the proposed SOP includes a complete emergency handling sequence, starting from the initial response, triage using the START system, basic medical intervention, to victim evacuation using the METTAG method.